An in vivo cross-linkable hyaluronan gel with inherent anti-inflammatory properties reduces OA cartilage destruction in female mice subjected to cruciate ligament transection. Issue 1 (January 2017) - Aulin, C.; Lundbäck, P.; Palmblad, K.; Klareskog, L.; Erlandsson Harris, H.
Summary: Objective: To explore the possibility of cartilage protection in osteoarthritis (OA) by intraarticular injection of a chemically modified hyaluronan (HA) gel and investigate whether the chemical modifications provide intrinsic anti-inflammatory activity. Method: OA was induced in C57BL/6 mice by anterior cruciate ligament transection (ACLT) and HA gel or carbazate-modified component was injected intra-articularly. Assessment of cartilage rescue was performed by histology, immunohistochemistry and TUNEL analysis. Serum levels of proinflammatory cytokines were evaluated with cytometric bead array, measuring IL-1β, TNF, IFN-γ, KC/CXCL1 and MCP-1. Results: Intraarticular injection of the HA gel showed significantly reduced cartilage destruction and decreased osteophyte formation. Besides the biological and biomechanical effects of HA, we investigated lipid peroxidation products as an alternative inflammatory and potential mechanism contributing to OA. To address this, injection of the carbazate-modified component alone was performed, which also demonstrated a cartilage-saving effect. Besides the cartilage amelioration effects, decreased apoptosis, 4-hydroxynonenal (4-HNE) and MHC class II staining was recorded. No changes in serum levels of proinflammatory cytokines were detected. Conclusion: We have shown that the HA gel has an anti-destructive effect on articular cartilage (AC). Our results demonstrated that the carbazate-modified component could suppress apoptotic events, potentially by quenching of ROS/LPO products such as 4-HNE in OA joints. Modification of the HA molecule offers opportunities to introduce (covalent) coupling of additional molecules to the gel, with controlled retention and subsequent release in the joint.